Xiaoyao Pills Attenuate Inflammation and Nerve Injury Induced by Lipopolysaccharide in Hippocampal Neurons In Vitro. (21st September 2020) - Fang, Yang; Shi, Boyu; Liu, Xiaobo; Luo, Jie; Rao, Zhili; Liu, Rong; Zeng, Nan
Abstract : Lipopolysaccharides (LPS) are proinflammation mediators that can induce the inflammatory model of the hippocampal neuron, and neuroinflammation participates in the pathophysiology of depression. Xiaoyao Pill is a classical Chinese medicine formula that has been used for the treatment of mental disorders such as depression in China since the Song dynasty. We established a hippocampal neuronal cell inflammation model by LPS and investigate the intervention effect and mechanism of Xiaoyao Pills. The expression levels of IL-6, TNF- α, IDO, 5-HT, brain-derived neurotrophic factor, and β -nerve growth factor were detected by enzyme-linked immunosorbent assay. mRNA levels of IL-6, TNF- α, 5-HT1A, IDO-1, brain-derived neurotrophic factor, nerve growth factor, tropomyosin receptor kinase B, tropomyosin receptor kinase A, and cAMP response element-binding protein were detected by reverse transcription-polymerase chain reaction. To further validate, protein expression was determined by western blot and immunofluorescence. Lipopolysaccharide-induced neuroinflammatory state resulted in the release of IL-6, TNF- α, and IDO and a decrease of BDNF, NGF, TrkB, TrkA, CREB, p-CREB, p-CREB/CREB, and SYP and inhibited hippocampal neurogenesis in the hippocampal neuron. Xiaoyao Pills significantly decreased the levels of IL-6, TNF- α, and IDO in cell supernatant and increased the expression of BDNF, NGF, TrkB, TrkA, CREB, p-CREB, p-CREB/CREB, and SYP as well as the average optical density of BrdU/NeuN double-labelled positive cells. Our study shows that lipopolysaccharides induce inflammation and nerve damage in hippocampal neurons, which are closely related to the pathological mechanism of depression. Xiaoyao Pills (XYW) play an important neuroprotective effect, which is related to its inhibition of neuronal inflammation and promoting the recovery of nerve injury. These results provide a pharmacologic basis for the treatment of depression of XYW in clinical application.